Beyond anticoagulant : Heparin as a potential anti-cancer agent - Ravi, Lokwani; Nina Suhaity, Azmi; Mashitah, Mohd Yusoff; Solachuddin Jauhari, Arief Ichwan (Hibiscus Publisher, 2014)
Heparin has been in the market since the last six decades due to its potential anticoagulant property. The mechanism of its anti-coagulation effect is well established. Along with its anticoagulant activity the other activity that is gathering a lot of importance now-a-days is its ability to arrest the progression of tumors specially some solid forms of tumors such as small cell lung carcinoma and pancreatic tumors. The chemically modified and light molecular weight fractions of heparin have been found to be more active in countering tumor progression. In this review we discuss a brief history of this versatile biomolecule with its clinical data and postulated mechanism of action as per recent studies. This review also highlighted the approach of heparin-conjugated nanoparticles to achieve targeted drug delivery with synergistic response in tumor cells.